Endothelial stromelysin1 regulation by the forkhead box-O transcription factors is crucial in the exudative phase of acute lung injury. (March 2019) - Artham, Sandeep; Gao, Fei; Verma, Arti; Alwhaibi, Abdulrahman; Sabbineni, Harika; Hafez, Sherif; Ergul, Adviye; Somanath, Payaningal R.
Graphical abstract: The suppression of Akt1 activity by LPS in pulmonary endothelial cells results in increased FoxO1/3a activation, in turn, leading to increased stromelysin1 expression/activity and reduced expression of tight junction proteins, particularly claudin5. Pharmacologically targeting FoxO or stromelysin activity inhibits LPS-induced pulmonary vascular injury and inflammation. Abstract: Enhanced vascular permeability is associated with inflammation and edema in alveoli during the exudative phase of acute respiratory distress syndrome (ARDS). Mechanisms leading to the endothelial contribution on the early exudative stage of ARDS are not precise. We hypothesized that modulation of endothelial stromelysin1 expression and activity by Akt1-forkhead box-O transcription factors 1/3a( FoxO1/3a) pathway could play a significant role in regulating pulmonary edema during the initial stages of acute lung injury (ALI). We utilized lipopolysaccharide (LPS)-induced mouse ALI model in vivo and endothelial barrier resistance measurements in vitro to determine the specific role of the endothelial Akt1-FoxO1/3a-stromelysin1 pathway in ALI. LPS treatment of human pulmonary endothelial cells resulted in increased stromelysin1 and reduced tight junction claudin5 involving FoxO1/3a, associated with decreased trans-endothelial barrier resistance as determined by electric cell-substrate impedance sensing technology. In vivo, LPS-induced lung edema was significantly higher in endothelial Akt1 knockdown ( EC-Akt1 –/– ) compared to wild-type mice, which was reversed upon treatment with FoxO inhibitor (AS1842856), stromelysin1 inhibitor (UK356618) or with shRNA-mediated FoxO1/3a depletion in the mouse lungs. Overall, our study provides the hope that targeting FoxO and styromelysin1 could be beneficial in the treatment of ALI.